Personal Values as Predictors of Perceived Organizational Values - Implications for Recruiters - Natarajan, N.K.; Nagar, Dinesh (Prabandhan: Indian Journal of Management, 2011)
This study was conducted as part of a larger study in a public sector organization, with an all India presence. This study explored if personal values predict perceived organizational values. 220 participants from a large public sector organization were asked to rate on a 7 point scale, the 24 items value taxonomy developed by McDonald&Gandz (1991, 1992) once as to how important these are to them as a guiding principle in their life, and once as how much they perceive their organization to promote these values. Results found that clusters of personal values are significantly correlated with clusters of perceived organizational values. Furthermore, specific clusters of personal values predict clusters of perceived organizational values. Since the value, congruence is related to positive work-related attitudes and behaviors, profiling a prospective employee's personal values at the time of recruitment may help in establishing likely personal-organization fit.